Making meaning through joint activity in Computer-Supported Collaborative Learning (CSCL) settings: The interplay between content-related and activity-related talk - Coll, César; Engel, Anna (Anales de Psicología / Annals of Psychology, 2014)
In the recent literature on CSCL which places the spotlight on participants’ talk, there is a clear dichotomy between studies that focus on content-related talk and those that focus on off-topic or activity-related talk. In the approach adopted in this paper, based on the notion of educational influence, the guiding hypothesis is that both forms of talk are closely linked in the collaborative dynamics and that activity-related talk, far from being irrelevant, has an essential role to play in promoting the collaborative construction of knowledge. The paper empirically examines this hypothesis in four online collaborative learning situations. The results show that participants in small group situations requiring the preparation of a written product devote a major part of their discursive activity to negotiating the form of organization of their joint activity and to making sure that all members are familiar with it. In contrast, the technological tools used in the collaborative situation do not seem to have an impact on the relative weight of the type of participants’ talk, either content-related or activity-related.